A novel operational approach to equipment maintenance: TPM and RCM jointly at work - Braglia, Marcello; Castellano, Davide; Gallo, Mosè (Journal of quality in maintenance engineering, 2019)
Purpose The purpose of this paper is to present a new operational approach to equipment maintenance designed to exploit the complementary nature of total productive maintenance (TPM) and reliability-centered maintenance (RCM). Design/methodology/approach This paper focuses on the operational aspect of the maintenance practice, proposing an equipment maintenance methodology that can be suitably adopted to define a new maintenance plan or check and improve an existing one. It integrates principles and methods of TPM and RCM and uses different tools to support decision-makers and operators. It proposes several worksheets which facilitate planning and implementing maintenance activities, that range from autonomous maintenance tasks to maintainability improvement actions. Findings This paper exploits the complementary nature of TPM and RCM to design or improve maintenance plans for a generic system. The tools and worksheets presented can be helpful to practitioners and operators. Originality/value While the integration of TPM and RCM is evidently a central issue in the maintenance management context, it has received limited attention in literature. To the best of the authors’ knowledge, it lacks a structured practical equipment maintenance methodology that exploits the complementary nature of TPM and RCM. Therefore, the approach presented in this paper would fill the current gap.